2021
DOI: 10.32413/pjph.v10i4.281
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Text Neck Pain in Islamabad

Abstract: Background: Neck pain is one of the most common musculoskeletal condition and causes most disability. Neck pain with movement coordinated impairments is the most common problem and among them “Text Neck Pain” is most growing epidemiological problem among adult population. Methods: This was the cross sectional study. The sample was collected from different Colleges and Universities of Islamabad. Sample was selected using convenient non-probability sampling technique. Data was collected from 428 individuals of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…A study conducted by Kumari et al reported a high prevalence of text neck syndrome with a mild prevalence of 36%, moderate 23.4%, and severe and complete text neck syndrome of 2.1% [3]. A local study also revealed the alarming nature of the condition with most population suffering neck pain using mobiles for more than 3 hours a day with a neck angle of 30-45 degrees [4]. Clinically text neck can present with neck stiffness, pain that is cutting and radiating, and general features, such as the area being sore, numb, and weak as well as headache [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Kumari et al reported a high prevalence of text neck syndrome with a mild prevalence of 36%, moderate 23.4%, and severe and complete text neck syndrome of 2.1% [3]. A local study also revealed the alarming nature of the condition with most population suffering neck pain using mobiles for more than 3 hours a day with a neck angle of 30-45 degrees [4]. Clinically text neck can present with neck stiffness, pain that is cutting and radiating, and general features, such as the area being sore, numb, and weak as well as headache [5].…”
Section: Introductionmentioning
confidence: 99%
“…It primarily affects the region extending from the lower margin of the mandible down to the suprasternal notch and the upper border of the clavicle (8). Among the various manifestations of neck pain, those associated with movement impairments are most common, with "Text Neck Pain" emerging as a burgeoning epidemiological concern among the adult population (9). The widespread use of mobile phones, often in ergonomically unfavorable postures, elevates the risk of physical injury (10), contributing to increased anxiety and worry among students in the absence of their smartphones (11).…”
Section: Introductionmentioning
confidence: 99%